Isolation and characterization of H3N8 equine influenza A virus associated with the 2011 epizootic in Mongolia. Issue 5 (4th January 2013) - Yondon, Myagmarsukh; Heil, Gary L.; Burks, John P.; Zayat, Batsukh; Waltzek, Thomas B.; Jamiyan, Bekh‐Ochir; McKenzie, Pamela P.; Krueger, Whitney S.; Friary, John A.; Gray, Gregory C.
Abstract : Background: Equine influenza virus (EIV) epizootics affect 2·1 million Mongolian horses approximately every 10 years and critically impact economy and nomadic livelihood of Mongolia. Objectives: An active surveillance program was established in 2011 to monitor influenza viruses circulating among Mongolian horses. Methods: Nasal swabs were collected from horses in free‐ranging horse herds in Töv, Khentii, and Dundgovi aimags (provinces) from January to September 2011. Real‐time reversetranscriptase–polymerase chain reaction (rRT‐PCR) was used to determine the presence of influenza A virus. Influenza A‐positive specimens were cultured to amplify virus; viral RNA was extracted, and gene segments were amplified and sequenced by Sanger sequencing. Results: A total of 745 horses were swabbed; most horses were without clinical signs of illness. In July 2011, reports of influenza‐like illnesses emerged among horses in Mongolia's capital, and subsequently, surveillance efforts were adjusted to swab horses associated with the epizootic. Thirty‐four specimens of rRT‐PCR influenza‐positive virus were collected in May, June, August, and September. Three specimens yielded detectable virus. Gene sequence studies suggested that all three isolates were identical H3N8 viruses. Phylogenetic analyses indicated the strain was very similar to other H3N8 EIVs circulating in central Asia between 2007 and 2008. Conclusions: As large Mongolian equine herds often seem to suffer from EIV epizootics, it seems prudent to continue such routine equine influenza surveillance. Doing so will provide an early warning system, should novel viruses emerge, help in assessing if EIV is crossing over to infect humans and provide data to assess the likely effectiveness of current EIV vaccines.